Indigenous women in Missions: silenced heritage - Jean Tiago Baptista; Camila Azevedo de Moraes Wichers; Tony Willian Boita (Revista Estudos Feministas, 2019)
In a discussion of the historical heritage of Jesuit Missions among Indigenous people (1609- 1750) based on theoretical and methodological concerns related to gender and heritage studies, this article addresses a) representations of indigenous women in historical documentation by Jesuits; b) resignification of the women’s spaces in archaeological sites currently open to visitation, such as the Archaeological Site of São Miguel Arcanjo; and c) issues arising from the relationship between gender and indigenous history, especially when applied to collections at museums dedicated to Missions. This work aims to demonstrate that a combined view of Mission heritage and indigenous women is possible.